2020
DOI: 10.1111/ddi.13196
|View full text |Cite
|
Sign up to set email alerts
|

High stream flows dilute environmental DNA (eDNA) concentrations and reduce detectability

Abstract: Aim Environmental DNA (eDNA) is a rapidly emerging methodology with important applications to environmental management and conservation. However, the effects of stream flow or discharge on eDNA have been minimally investigated in lotic (stream and river) environments. In this study, we examined the role of stream flow on eDNA concentrations and detectability of an invasive clam (Corbicula fluminea), while also accounting for other abiotic and biotic variables. Location Illinois, United States of America. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 70 publications
8
64
0
Order By: Relevance
“…However, LMM analysis indicated that there is a difference in eDNA detectability between winter and summer samples both with regard to detection rate and eDNA concentration (Figures 2, 3). This result is in line with previous studies, showing that eDNA detectability can be affected by season, depending on the biology of the target species (e.g., reproduction period, activity) (Buxton et al, 2018;Curtis et al, 2020). For crayfish, reduced detection rates in winter were an anticipated effect, since all European crayfish species show reduced activity and metabolism during winter (Bubb et al, 2002), which likely results in reduced eDNA shedding rates.…”
Section: Spatio-temporal Effects On Edna Detectabilitysupporting
confidence: 91%
See 2 more Smart Citations
“…However, LMM analysis indicated that there is a difference in eDNA detectability between winter and summer samples both with regard to detection rate and eDNA concentration (Figures 2, 3). This result is in line with previous studies, showing that eDNA detectability can be affected by season, depending on the biology of the target species (e.g., reproduction period, activity) (Buxton et al, 2018;Curtis et al, 2020). For crayfish, reduced detection rates in winter were an anticipated effect, since all European crayfish species show reduced activity and metabolism during winter (Bubb et al, 2002), which likely results in reduced eDNA shedding rates.…”
Section: Spatio-temporal Effects On Edna Detectabilitysupporting
confidence: 91%
“…Finally, water volume, e.g. during flood conditions, has been found to influence eDNA detectability (Curtis et al, 2020). This might imply an influence of stream size on crayfish eDNA detectability, which, however, has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method can be applied to detect other species of Podostemaceae in Japan. Although it was raining at the time of the 2019 survey, which can dilute eDNA concentrations and lead to false negatives for target species (Curtis et al, 2020;Sales et al, 2021), Podostemaceae eDNA was detectable in all samples near known habitats. Therefore, the method employed in this study seems to be effective under various weather conditions.…”
Section: Usefulness Of Edna Survey For Determining the Distribution Of Podostemaceaementioning
confidence: 99%
“…Curtis et al. (2021) investigated the role of water flow on eDNA concentrations and subsequent effects on the detectability of an invasive freshwater clam ( Corbicula fluminea ) in streams across seasons. Their results indicated that higher stream flows decreased eDNA concentrations and that stream floods increased the rate of false negatives (i.e.…”
Section: This Issuementioning
confidence: 99%